Analysis of Factors Influencing Compliance with the Implementation of the Surgical Safety Checklist in the Central Surgery Installation (CSI) at Imelda General Hospital for Indonesian Workers - Lumbantobing, Salomo; Nasution, Sri Wahyuni; Ginting, Chrismis Novalinda (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
One indicator of the quality of service to patients is patient safety, where hospitals have an obligation to create a system that reduces or even prevents incidents that threaten patient safety. Surgical safety checklist or abbreviated as SSC is a patient safety procedure in the form of a checklist created by WHO as the basis for the actions carried out by the surgical team in the operating room. The aim of this research is to analyze the factors that influence nurses' compliance in implementing the Surgical Safety Checklist (SSC) in the Central Surgical Installation (IBS) of RSU Imelda Workers Indonesia. This type of research is quantitative research that uses a correlational design. The method used in this research is a cross sectional approach. In this study, the population was 25 nursing staff who worked at the Central Surgical Installation (IBS) of RSU Imelda Workers Indonesia. Sampling in this research was carried out using a non-probability sampling technique with a total sampling approach, which refers to sampling by taking all members of the population as samples, namely 25 respondents. The data analysis used is univariate, bivariate and multivariate analysis. The research results show that there is an influence of knowledge, work stress and workload on compliance with the implementation of the Surgical Safety Checklist (SSC) in the Central Surgical Installation (IBS) of the Indonesian Workers' Imelda Hospital. There is no effect of length of work on compliance with the implementation of the Surgical Safety Checklist (SSC) in the Central Surgical Installation (IBS) of RSU Imelda Workers Indonesia. The independent variable in this study that has the most influence on compliance with the implementation of the Surgical Safety Checklist (SSC) in the Central Surgical Installation (IBS) of RSU Imelda Workers Indonesia is the workload variable (X3).